Changing lives?: desistance research and offender management - McNeill, Fergus (Report, 2010)
This report provides a literature review on desistance from crime which explores the purposes of offender management; understanding and supporting desistance; desistance and the process of offender management; desistance and compliance with offender management; and, desistance and the credibility of offender management. The review was commissioned by the National Offender Management Service (NOMS) to open up lines of enquiry which NOMS may then pursue through its policy programme – specifically its emerging work on offender engagement. The report was commissioned and should be interpreted not as a systematic literature review of desistance research, but rather as a deliberately discursive and speculative paper which aims to scope out some of the implications of desistance research for offender management, rather than to make any definitive statement either about desistance research or about its interpretation in practice.